A Grape Powder Attenuates Colonic Inflammation, Inhibits Colitis-associated Colorectal Cancer Development and Causes Favorable Changes of Gut Microbiota in Mice (OR04-07-19). (13th June 2019) - Zhao, Yiying; Nakatsu, Cindy; Jiang, Qing
Abstract: Objectives: Recent discoveries suggest that gut microbiota is involved in the progression of colitis-associated colorectal cancer (CAC) and natural products like polyphenols can modulate gut microbiota. Polyphenol components of grape like resveratrol have been shown to have anti-colorectal cancer effects in animal models, but the underlying mechanism is not completely understood. The objective of this study is to examine the chemo-preventive effect of a whole grape powder (GP) on tumorigenesis in a mouse CAC model and evaluated the impact of GP on gut microbiota as a potential anti-CAC mechanism. To dissect the role of polyphenols in the GP, we compared GP at 3 and 10% diet to calorie, fiber, sugar and organic acid-matched placebo. Methods: We used male Balb/c mice and divided them into diseased groups treated with azoxymethane (AOM) and dextran sodium sulfate (DSS) and healthy groups, both of which had placebo control diet, GP at 3% or 10% diet. To induce tumorigenesis, we injected AOM at 9.5 mg/kg bw at 6 weeks of age, followed by 2-cycle DSS (1.5% in drinking water). During the study, we monitored animals' body weight and food consumption weekly, and evaluated their colitis symptoms during DSS treatments. All animals were sacrificed at 16 weeks of age and 24-hr accumulative fecal samples were collected prior to sacrifice for gut microbial analysis. Results: Compared to the control diet, 10% GP diet alleviated colitis symptoms including rectal bleeding and diarrhea, and reduced total tumor multiplicity by 29% ( P  < 0.05). GP diet increased microbial alpha-diversity and significantly shifted the gut microbial composition in both healthy and diseased groups. Under both conditions, 10% GP diet increased the abundance of various taxa belonging to Lachnospiraceae family. Canonical correspondence analysis (CCA) of gut microbiota indicated that increased GP supplementation was associated with healthier animal status. In particular, we observed that the predicted functional profile of gut microbiota from diseased mice with 10% GP diet was similar to those from healthy mice with the control diet. Conclusions: 10% GP diet showed CAC chemo-preventive effects and modulated gut microbiota under both healthy and diseased conditions, and appeared to prevent CAC-associated gut microbiota changes. Funding Sources: California Table Grape Commission.